STATISTICAL ANALYSIS OF THE SEASONAL VARIATION OF MOLDOVAN MIGRANTS’REMITTANCES DURING THE PERIOD 2003-2013 - Balan, Christiana; Jaba, Elisabeta; Pârţachi, Ion; Chistrugă, Boris (Studies and Scientific Researches. Economics Edition, 2014)
As a consequence of the increased number of Moldovan migrants, the volume of remittances inflows to Moldova raised steadily. Previous studies on labor migration and remittances in Republic of Moldova underline both the role of remittances in generating increased consumption of the population and its impact on the economic development of the country. In this paper, we aim to analyze the variation of money transfers of Moldovan migrants in order to estimate the trend of the remittances inflows and the seasonal variations under the impact of the global crisis. The data on remittances are available from the National Bank of Moldova, on a monthly basis, for the time span 2003-2013. The study’s results highlight an upward trend and the seasonal variation of money transfer of Moldovan migrants for the considered time span.